GOVERNMENT EFFORTS TO IMPROVE ECONOMIC INEQUALITY IN THE FRAMEWORK OF INDONESIA'S ECONOMIC EQUITY - Meiryani Meiryani; Danesa Reynard Setiawan (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2022)
The purposes of this paper are to find out the phenomena that prove that the Indonesian economy is uneven, to find out the government's efforts in improving the distribution of the Indonesian economy, to find out the ways that the government is doing to improve the distribution of the Indonesian economy, and to find out the results of the government's efforts to improve economic equity in Indonesia. The data is collected and analyzed from the Badan Pusat Statistics's website and journals to develop theoretical foundations for the problem. The result of this paper indicates that the Economic Equity Policy does not always produce results, the government and all Indonesian people must be able to justify or reduce this inequality in various ways. Of course, this process is neither instant nor easy because this inequality is not a problem that can be done alone and will take a long time.